3D printed micro-scale force gauge arrays to improve human cardiac tissue maturation and enable high throughput drug testing. (1st September 2019) - Ma, Xuanyi; Dewan, Sukriti; Liu, Justin; Tang, Min; Miller, Kathleen L.; Yu, Claire; Lawrence, Natalie; McCulloch, Andrew D.; Chen, Shaochen
Graphical abstract: Abstract: Human induced pluripotent stem cell – derived cardiomyocytes (iPSC-CMs) are regarded as a promising cell source for establishing in-vitro personalized cardiac tissue models and developing therapeutics. However, analyzing cardiac force and drug response using mature human iPSC-CMs in a high-throughput format still remains a great challenge. Here we describe a rapid light-based 3D printing system for fabricating micro-scale force gauge arrays suitable for 24-well and 96-well plates that enable scalable tissue formation and measurement of cardiac force generation in human iPSC-CMs. We demonstrate consistent tissue band formation around the force gauge pillars with aligned sarcomeres. Among the different maturation treatment protocols we explored, 3D aligned cultures on force gauge arrays with in-culture pacing produced the highest expression of mature cardiac marker genes. We further demonstrated the utility of these micro-tissues to develop significantly increased contractile forces in response to treatment with isoproterenol, levosimendan, and omecamtiv mecarbil. Overall, this new 3D printing system allows for high flexibility in force gauge design and can be optimized to achieve miniaturization and promote cardiac tissue maturation with great potential for high-throughput in-vitro drug screening applications. Statement of Significance: The application of iPSC-derived cardiac tissues in translatable drug screening is currently limited by the challenges in forming mature cardiac tissue and analyzing cardiac forces in a high-throughput format. We demonstrate the use of a rapid light-based 3D printing system to build a micro-scale force gauge array that enables scalable cardiac tissue formation from iPSC-CMs and measurement of contractile force development. With the capability to provide great flexibility over force gauge design as well as optimization to achieve miniaturization, our 3D printing system serves as a promising tool to build cardiac tissues for high-throughput in-vitro drug screening applications.